Pengaruh Semangat Kerja, Self Efficacy dan Kepuasan Kerja Terhadap Quality of Work Life Karyawan Fashion Store Yogyakarta - Trilvita, Landriana; Kirana, Kusuma Chandra (Universitas Batanghari Jambi, 2024)
The main concern of this study is to find out (1) how the morale of employees in Fashion Story affects the quality of their work life. (2) How self-efficacy affects the quality of their work life when working at Fashion Story and (3) job satisfaction at Fashion Story Yogyakarta, and its impact on employee welfare. One hundred and fifty workers from Fashion Story Yogyakarta constitute the study population. An error of no more than 10% is allowed when calculating the research sample using the slovin formula. So, 60 employees are randomly selected to participate in the survey. Each component of the Likert scale questionnaire used for data collection has previously been validated for validity and reliability. The t-test and r-test, along with other conventional assumptions and hypothesis tests, were used in the data analysis. One of the findings of this study is that employee morale has no effect on QWL. There is a positive and statistically significant relationship between self-efficacy measures and job satisfaction with their work at Fashion Story.